2018
DOI: 10.2807/1560-7917.es.2018.23.11.18-00106
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of yellow fever infections among unvaccinated European travellers due to ongoing outbreak in Brazil, July 2017 to March 2018

Abstract: Since December 2016, Brazil has faced a large outbreak of yellow fever with ca 1,500 confirmed human cases. In the first 2 months of 2018, Brazil reported almost as many cases as in 2017 as a whole. In these 2 months, five imported cases were reported among unvaccinated European travellers. Three had travelled to Ilha Grande, a popular destination among European tourists. Physicians and European travellers visiting Brazil should follow yellow fever vaccination recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 5 publications
1
19
0
2
Order By: Relevance
“…ferox , Sabethes chloropterus and Sabethes soperi are known vectors in sylvatic Yellow Fever cycles (Hanley et al 2013; Abreu et al 2019). It is important to document the occurrences of such species, especially as several studies have reported on Yellow Fever outbreaks near natural areas (Fujita et al 2018; Gossner et al 2018; Hamer et al 2018; Giovanetti et al 2019 ; Siqueira et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ferox , Sabethes chloropterus and Sabethes soperi are known vectors in sylvatic Yellow Fever cycles (Hanley et al 2013; Abreu et al 2019). It is important to document the occurrences of such species, especially as several studies have reported on Yellow Fever outbreaks near natural areas (Fujita et al 2018; Gossner et al 2018; Hamer et al 2018; Giovanetti et al 2019 ; Siqueira et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Between January and March 2018, 11 unvaccinated cases have been reported in travellers returning from Brazil, excluding case 2 but including case 1 presented here [1]. The cases were from France, the Netherlands, Switzerland, Romania, the United Kingdom, Argentina and Chile [1,2] and are described in more detail in Table. Eight of the 11 cases had travelled to Ilha Grande and four died [2]. Since 2016, YF cases have increased in international travellers compared with the past 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…Among international travellers in South America, five cases, including two deaths, were reported between July 2016 and March 2017 [4][5][6]. In January and February 2018, 11 cases have been declared according to the latest updates, including one of the cases presented in this article [1,2]. Here we report details of two cases of YF in unvaccinated French travellers in Brazil in January and March 2018, respectively.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the Angola outbreak resulted in spread to the Democratic Republic of the Congo (DRC) [13], Mauritania and Kenya [14], as well as importation of disease into China by unvaccinated Chinese nationals who were infected while working in Angola [15,16]. In South America, a large urban outbreak was detected in 2016 in a non-endemic area of Brazil, and from 2016 to March of 2019 there were 2204 reported human cases or more cases than in the previous 20 years combined [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%